PENGEMBANGAN ACADEMIC INFORMATION DASHBOARD EXECUTIVE (A-INDEX) DENGAN PENTAHO DATA INTEGRATION DAN QLIKVIEW - Herry Sofyan; Simon Pulung Nugroho (Telematika, 2016)
Information Dashboard Executive (INDEX) is a visual representation of data in the form of dashboards that are used to get a snapshot of performance in every business process so as to facilitate the executives took a quick response. Pentaho is a BI application is free open source software (FOSS) and runs on top of the Java platform. QlikView is focused on simplifying decision making for business users across the organization. Processing needs to be able to optimize data analysis functions of PDPT is developing an interactive dashboard visualization data. The dashboard will be built using the data pentaho integration as a gateway connecting between database applications with Data PDPT and data visualization are developed by using QlikView. Software development methodologies in application development work is incremental method which is a combination of linear and iterative method with parallel modifications in the process the iterative process so that the project done faster.The results of this study are is the data representation of the modeling query is constructed able to describe the activity / student profiles in a certain semester. The data representations constructed include active distribution per class, per student graduation force distribution, distribution of student status, distribution provinces of origin of students per class, the distribution of the number of class participants, distribution of credits lecturers and distribution of subject.